A 3D Smale Horseshoe in a Hyperchaotic Discrete-Time System. (24th January 2007) - Li, Qingdu; Yang, Xiao-Song
Abstract : This paper presents a three-dimensional topological horseshoe in the hyperchaotic generalized Hénon map. It looks like a planar Smale horseshoe with an additional vertical expansion, so we call it 3D Smale horseshoe. In this way, a computer assisted verification of existence of hyperchaos is provided by means of interval analysis.